2021
DOI: 10.3389/fonc.2020.584683
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Cells Alter Adipogenesis, Increase Senescence-Related and Inflammatory Gene Transcript Expression, and Alter Metabolism in Preadipocytes

Abstract: Within the bone marrow microenvironment, mesenchymal stromal cells (MSCs) are an essential precursor to bone marrow adipocytes and osteoblasts. The balance between this progenitor pool and mature cells (adipocytes and osteoblasts) is often skewed by disease and aging. In multiple myeloma (MM), a cancer of the plasma cell that predominantly grows within the bone marrow, as well as other cancers, MSCs, preadipocytes, and adipocytes have been shown to directly support tumor cell survival and proliferation. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…IL-6, TGFβ) that may in uence the local breast microenvironment in a manner that contributes to cancer progression. Age, obesity and cancer have been shown to be drivers of senescence and/or an adipogenesis defect in ASCs [19][20][21][22]. In the current study, we observed a senescent bASC phenotype in both pre-menopausal (patients D, F, and H) and post-menopausal (patients, C, E, and G) women.…”
Section: Discussionsupporting
confidence: 64%
“…IL-6, TGFβ) that may in uence the local breast microenvironment in a manner that contributes to cancer progression. Age, obesity and cancer have been shown to be drivers of senescence and/or an adipogenesis defect in ASCs [19][20][21][22]. In the current study, we observed a senescent bASC phenotype in both pre-menopausal (patients D, F, and H) and post-menopausal (patients, C, E, and G) women.…”
Section: Discussionsupporting
confidence: 64%
“…Myeloma cells may regulate adipogenesis in order to sustain their survival and homing in the bone marrow milieu [ 118 ]. Myeloma cells induce the expression of genes related to an inflammatory state and a senescence associated secretory phenotype (SAPS) in the adipocytes, in order to promote myelomatogenesis and myeloma cell survival [ 119 ]. Interestingly, the response to treatment may restore the adipocyte homeostasis in the bone marrow [ 120 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Dr. Podgorski concluded her talk by stressing an importance of understanding the role of BMAT in tumor adaptation and survival in bone, as a tool to reveal novel, mechanistic targets for therapies for prostate and breast bone-metastatic diseases, which continue to be incurable (27). After this, Emma Morris discussed the effects of PPARg agonist BAGDE on myeloma cells and bone marrow adipocytes (28), Sonia Severin showed a functional link between marrow adipocytes and the development of megakaryocytes (29), and Mariah Farrell revealed that bone marrow adipocytes support multiple myeloma drug resistance and induce adipocyte mimicry, increasing cell survival (30,31). Overall, this session stressed an importance of understanding the role of BMAT in hematopoiesis and cancer cell survival in bone, while underscoring a prominent role of adipocytes in the regulation of different components of hematopoietic niche.…”
Section: Session Iv: Advanced Methods For Clinical and Pre-clinical Assessment Of Bone Marrow Adiposity And Skeletal Healthmentioning
confidence: 99%